The Actin Network Interfacing Diverse Integrin-Mediated Adhesions - Benjamin Geiger; Rajaa Boujemaa-Paterski; Sabina E. Winograd-Katz; Jubina Balan Venghateri; Wen-Lu Chung; Ohad Medalia (Biomolecules, 2023)
The interface between the cellular actin network and diverse forms of integrin-mediated cell adhesions displays a unique capacity to serve as accurate chemical and mechanical sensors of the cell’s microenvironment. Focal adhesion-like structures of diverse cell types, podosomes in osteoclasts, and invadopodia of invading cancer cells display distinct morphologies and apparent functions. Yet, all three share a similar composition and mode of coupling between a protrusive structure (the lamellipodium, the core actin bundle of the podosome, and the invadopodia protrusion, respectively), and a nearby adhesion site. Cytoskeletal or external forces, applied to the adhesion sites, trigger a cascade of unfolding and activation of key adhesome components (e.g., talin, vinculin, integrin), which in turn, trigger the assembly of adhesion sites and generation of adhesion-mediated signals that affect cell behavior and fate. The structural and molecular mechanisms underlying the dynamic crosstalk between the actin cytoskeleton and the adhesome network are discussed.